Surface Morphology and Optical Characterization of OC1 OC6-PPV Films - C. A. Olivati (Brazilian Journal of Physics, 2006)
We report optical and morphological properties of poly(2-methoxy-5-hexyloxy-p-phenylenevinylene)(OC1OC6-PPV) films processed by casting, spin-coating (SC) and Langmuir-Blodgett (LB) techniques. Theabsorption spectra are practically the same, with an absorption maximum at approximately at 500 nm. For thephotoluminescence (PL) spectra at low temperature (T=10K), a small but significant difference was noted in thecast film, in comparison with the LB and SC films. The zero-phonon transition shifted from 609 nm for the LBfilm to 615 and 621 nm for the SC and cast films, respectively. At room temperature, the PL spectra are similarfor all films, and blue shifted by ca. 25 nm in comparison with the spectra at low temperature due to thermaldisorder. Using atomic force microscopy (AFM) we inferred that the distinctive behavior of the cast film, probablyassociated with structural defects, is related to the large thickness of this film. The surface roughness, whichwas surprisingly higher for the LB film, apparently played no role in the emission properties of OC1OC6-PPVfilms.